The EFFECT OF PERSONAL SELLING, SALES PROMOTION AND PRODUCT QUALITY ON THE PURCHASE DECISION OF YUASA BRAND MOTOR BATTERY AT PT ADIDAYA KARYA INDOTAMA MEDAN - Willy Hadinata; Jeffrey Jeffrey; Ryan Trizie; Jarungjung Hutagaol (SEAN Institute, 2023)
The research was conducted at PT Adidaya Karya Indotama Medan. The research objective was to examine and analyze the influence of Personal Selling, Sales Promotion and Product Quality on Purchase Decisions of Yuasa Brand Battrey Motors at PT Adidaya Karya Indotama Medan.;Population;amounted to 167 customers and the number of samplesgas many as 118 customers. Technique;sampling;used is;random sampling;sampling. The results of the partial test obtained tcount > ttable or 2.155 > 1.981 and it was significant that 0.033 <0.05, meaning that Ha was accepted Ho was rejected. namely Personal Selling has a positive and significant partial effect on the Purchase Decision of the Yuasa Brand Battrey Motor at PT Adidaya Karya Indotama Medan. The partial test results obtained tcount > ttable or 3.557 > 1.981 and it was significant that 0.001 <0.05, meaning that Ha was accepted Ho was rejected. namely Sales Promotion has a positive and significant effect partially on the Purchase Decision of Yuasa Brand Motor Battrey at PT Adidaya Karya Indotama Medan. The partial test results obtained tcount > ttable or 2.771 > 1.981 and it was significant that 0.007 <0.05, meaning that Ha was accepted Ho was rejected. namely Product Quality has a positive and significant partial effect on the Purchase Decision of the Yuasa Brand Motor Battrey at PT Adidaya Karya Indotama Medan Simultaneous test results obtained F count (9.910) > F table (2.68) and a significance probability of 0.000 <0.05, meaning that Ha is accepted Ho is rejected, so it is concluded that Personal Selling, Sales Promotion and Product Quality have a positive and significant effect simultaneously on the Purchase Decision of the Yuasa Brand Battrey Motor at PT Adidaya Karya Indotama Medan